A tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst, its preparation method and application
Patent Information
- Application Number
- CN202611194423.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-30
AI Technical Summary
此外,如何在构建高活性多元异质结的同时,对其微观形貌特征(如高效的多级中空管状通道)进行精准且稳定的协同调控,依然是目前制备技术难以攻克的形貌控制瓶颈
(1)本发明针对水环境中四环素类抗生素的高效降解需求,结合纤维素载体优势,通过化学镀、高温氧化与水热硫化法成功制备了管状CuO/Cu2O-Cu7S4三元异质结光催化剂。TEM、XRD及XPS表征证实了三相组分的紧密耦合,O 1s与Cu 2p的规律性峰偏移证实了电子的定向迁移,标志着S-型异质结的成功构建。
Smart Images

Figure CN122999222A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalyst technology, and more specifically to a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst, its preparation method, and its application. Background Technology
[0002] With the expansion of the global aquaculture and pharmaceutical industries, the overuse of tetracycline antibiotics has led to their persistent residues in the aquatic environment, reaching concentrations from μg / L to mg / L. These pollutants are bioaccumulative, inducing antibiotic resistance genes (ARGs) in bacteria and threatening ecological security and human health through the food chain. Antibiotic pollution in water bodies has become a global environmental problem. Therefore, developing efficient and economical water treatment technologies to remove tetracycline antibiotics from water bodies is particularly important. In recent years, photo / Fenton-like systems, which couple photocatalysis and Fenton-like technology, have become a research hotspot due to their high efficiency and selectivity in degrading organic pollutants, breaking through the application bottleneck of single advanced oxidation technologies. The core of this system lies in utilizing photogenerated electrons generated during photocatalysis to accelerate the valence state cycling rate of transition metal ions (such as Cu). 2+ / Cu + This significantly improves the generation efficiency of reactive oxygen species (ROS) within the system. Among them, copper (Cu)-based oxides possess reversible Cu... 2+ / Cu + Redox pairs significantly outperform traditional iron-based catalysts in activating persulfate (PMS) in Fenton-like reactions. To further improve the efficiency of photogenerated charge transport, heterojunctions constructed by combining copper oxides with narrow-bandgap copper sulfides are commonly used. However, powdered copper nanocomposites are prone to spontaneous aggregation in practical applications, leading to deep burial of active sites and difficulty in recovery in continuous flow reactors, resulting in easy loss and secondary metal contamination. Therefore, finding suitable supports for catalyst immobilization and structural optimization has become crucial for improving their performance. Existing copper-based photocatalytic / Fenton-like composite materials still face several challenges in practical applications, including:
[0003] 1. Uneven distribution of active components, severe agglomeration, and difficulty in constructing microscopic hierarchical structures: Existing co-precipitation or hydrothermal methods for preparing binary or ternary copper-based composite materials result in nanoparticles that are prone to spontaneous, disordered agglomeration during synthesis due to their high surface energy. This not only deeply buries active catalytic sites and drastically reduces specific surface area but also significantly hinders the diffusion of reactants (such as persulfates and antibiotic molecules) to the catalyst's reactive surface. Furthermore, how to precisely and stably control the microscopic morphology (such as efficient hierarchical hollow tubular channels) while constructing highly active multi-component heterostructures remains a bottleneck in morphology control that current preparation techniques struggle to overcome.
[0004] 2. High interfacial impedance and obstructed photogenerated electron transport channels: Although heterojunction interfaces can be constructed by combining copper oxides and copper sulfides, composite materials prepared by conventional methods often lack long-range ordered charge transport channels. Photogenerated electrons are prone to secondary recombination when migrating between amorphous, disordered, or poorly contacted phase interfaces, resulting in extremely high interfacial charge transport impedance. This hinders the development of Cu... 2+ To Cu + The severely insufficient number of effective electrons in the reduction directly limits the reduction of Cu. 2+ / Cu + Directional acceleration of in-situ redox cycles cannot maximize the synergistic catalytic activity of photocatalysis / Fenton-like processes.
[0005] 3. Performance Defects of Traditional Carriers and Bottlenecks in the Functional Utilization of Green Biomass Carriers (Cellulose): To address the problems of easy loss, difficulty in recycling, and secondary metal pollution of powdered catalysts, the introduction of carriers for immobilization is a mainstream trend. However, existing traditional inorganic (such as silica, alumina, and molecular sieves) or carbon-based (such as carbon nanotubes) carriers generally suffer from drawbacks such as complex preparation processes, high costs, and poor flexibility. Furthermore, their surfaces lack sufficient active coordinating groups, resulting in extremely weak interfacial bonding with active components. Under prolonged impact from highly oxidizing water, active components are easily detached, leading to a sharp drop in catalytic activity. Although green biomass carriers (such as cellulose rich in hydroxyl groups and with a hierarchical porous structure) have excellent dispersion and anchoring advantages, current technologies only use them as simple physical supports, typically employing direct impregnation or simple physical mixing. This not only results in the disordered accumulation of active components on the cellulose surface, failing to leverage the unique morphological template guiding role of cellulose, but also makes it difficult to establish directional charge transport channels on the cellulose substrate, limiting the application efficiency of cellulose-based composite materials in practical wastewater treatment.
[0006] Therefore, how to provide a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst, its preparation method, and its application is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0007] In view of this, this invention combines the structural advantages of cellulose with the catalytic properties of copper-based oxides. Using cellulose as a substrate, a multi-step process involving chemical copper plating, high-temperature oxidation, and hydrothermal sulfidation was employed to successfully prepare a CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst with a tubular structure. This constructs a photo / Fenton-like system, utilizing the synergistic effect between the multi-component copper-based oxide / sulfide to broaden the photoresponse range and accelerate the electron transfer process and free radical generation efficiency in the photo / Fenton-like synergistic reaction. This enables rapid activation of PMS and efficient degradation of antibiotics under visible light, providing a novel material and technical solution for the efficient treatment of water pollution, which is of great significance for environmental protection and water pollution control.
[0008] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst includes the following steps: (1) Cellulose was dispersed in distilled water to form a suspension system. The suspension system was then subjected to a separation process using an ultrasonic cell disruptor. The product was then collected by filtration to obtain ultrasonically pretreated cellulose. (2) Prepare activation solution A, activation solution B and two identical chemical plating solutions; then, perform surface activation of the ultrasonically pretreated cellulose in the two activation solutions; after activation, filter out the solid and put it into the two chemical plating solutions for two-stage chemical plating treatment. Finally, obtain cellulose with deposited Cu by filtration, drying and sieving. (3) Place the cellulose with deposited Cu in a muffle furnace, heat and keep it at a constant temperature, cool it to room temperature and take it out to obtain a tubular CuO-Cu2O composite product; (4) Take the tubular CuO-Cu2O composite product and put it into the reaction vessel. Add thiourea and then add anhydrous ethanol as the reaction medium. Stir magnetically until the system is mixed evenly and there is no obvious particle agglomeration. (5) Place the reactor in a constant temperature oven, heat it up and keep it at the temperature to carry out the hydrothermal reaction; after the reaction is completed, cool it to room temperature and take out the sample; wash the sample alternately with deionized water and anhydrous ethanol, dry it, and obtain the final product.
[0009] Preferably, in step (1), the ultrasonic power of the stripping process is 400-600 W, the ultrasonic interval is 3 s, and the time is 1-2 h.
[0010] Preferably, in step (2), the composition of the activation solution A is: 2.4 mL of concentrated hydrochloric acid and 3 g of copper sulfate pentahydrate added to every 200 mL of distilled water; The composition of the activation solution B is: 2.4 g sodium hydroxide and 3 g sodium borohydride are added to every 200 mL of distilled water; The chemical plating solution is composed of: 15.9 g copper sulfate pentahydrate, 3.9 g potassium sodium tartrate, 8.1 g disodium ethylenediaminetetraacetate, 0.9 g potassium ferrocyanide, and 21 mL formaldehyde solution added to every 300 mL of distilled water.
[0011] Preferably, in step (2), the specific operation of surface activation is as follows: first place it in activation solution A and stir for 15 min, then transfer it to activation solution B and react for 90 s; Each electroless plating process lasts for 30 minutes.
[0012] Preferably, in step (3), the temperature is heated to 300-350°C and kept at a constant temperature for 6 hours.
[0013] Preferably, in step (4), the mass ratio of the tubular CuO-Cu2O composite product to thiourea is 10:1-6; The magnetic stirring time is 30 minutes.
[0014] Preferably, in step (5), the heating rate is 5℃ / min, and the temperature is maintained at 170℃ for 16 h.
[0015] The present invention also provides a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst obtained by the above preparation method.
[0016] This invention also provides the application of the above-mentioned tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst in the activation of PMS for the degradation of tetracycline antibiotics in water.
[0017] Preferably, the tetracycline antibiotics include tetracycline (TC) and oxytetracycline (OTC).
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention addresses the need for efficient degradation of tetracycline antibiotics in aquatic environments. Leveraging the advantages of cellulose as a carrier, a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst was successfully prepared via chemical plating, high-temperature oxidation, and hydrothermal sulfidation. TEM, XRD, and XPS characterization confirmed the tight coupling of the three phases, and the regular peak shifts between O 1s and Cu 2p confirmed the directional migration of electrons, marking the successful construction of the S-type heterojunction.
[0019] (2) In the visible light-driven photocatalytic / Fenton-like system, the product COS-3 exhibited the best activity, with degradation rates of 39.8% and 43.6% for TC and OTC, respectively. After the introduction of PMS, the synergistic effect led to an explosive increase in the degradation rate. Within 20 min, the removal rates of TC and OTC reached as high as 94.9% and 95.7%, respectively, which were 2.38 and 2.19 times higher than those of the single photocatalytic system.
[0020] (3) Mechanism studies revealed that the S-type heterojunction significantly promoted the spatial separation of photogenerated carriers, and the high-energy electrons enriched on the Cu7S4 surface accelerated the Cu 2+ / Cu + Redox cycle, thereby efficiently activating PMS to produce SO42-. - It is dominated by reactive oxide species. ECOSAR assessment further confirmed that this system can mineralize antibiotics into low-toxicity products, demonstrating excellent environmental safety and application prospects.
[0021] (4) The process of this invention is simple, the preparation cost is low, and it has good recyclability, making it suitable for long-term application. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0023] Figure 1 (a) is a TEM image of COS-3; Figure 1 (b) is a SEM image of COS-3; Figure 1 (c) is the EDS plot of COS-3; Figure 1 (d) shows the XRD patterns of different materials; Figure 1 (e) shows the adsorption isotherms of different materials; Figure 1 (f) shows the pore size distribution of different materials.
[0024] Figure 2 (a) is the total spectrum of COS-3; Figure 2 (b) shows the fine O 1s spectrum of COS-3; Figure 2 (c) shows the fine Cu 2p spectrum of COS-3; Figure 2 The middle (d) image shows the fine C 1s spectrum of COS-3; Figure 2 (e) is the fine O 1s spectrum of CuO-Cu2O; Figure 2In the middle (f), the Cu 2p spectrum of CuO-Cu2O is shown. Figure 2 (g) is the fine S 2p spectrum of COS-3; Figure 2 The middle (h) image is the fine S 2p spectrum of Cu7S4; Figure 2 In the middle (i), Cu 2p fine spectrum of Cu7S4 is shown.
[0025] Figure 3 (a) shows the diffuse ultraviolet reflectance of different materials; Figure 3 (b) shows the band gap diagrams for different materials; Figure 3 XPS valence band spectra of CuO-Cu2O in (c) Figure 3 (d) is the XPS valence band spectrum of Cu7S4; Figure 3 (e) shows the electrochemical impedance spectroscopy diagrams for different materials; Figure 3 In the middle (f), the transient photocurrent diagrams of different materials are shown.
[0026] Figure 4 In the middle (a), the degradation performance of TC by different materials is shown; Figure 4 (b) shows the degradation performance of different materials on OTC; Figure 4 (c) represents the degradation amount of TC by different materials; Figure 4 In the middle (d), the degradation amount of OTC by different materials is represented; Figure 4 In the equation (e), the reaction rate constants of different materials with TC are represented. Figure 4 In the equation (f), we find the reaction rate constants of different materials with OTC.
[0027] Figure 5 (a) shows the degradation performance of TC by different amounts of PMS; Figure 5 (b) shows the degradation performance of OTC with different amounts of PMS; Figure 5 (c) represents the degradation of TC by different amounts of PMS; Figure 5 (d) represents the degradation of OTC by different amounts of PMS; Figure 5 In the figure (e), the reaction rate constant of TC is given by different amounts of PMS addition. Figure 5 In the equation (f), we find the reaction rate constant of OTC with different amounts of PMS.
[0028] Figure 6 In the middle (a), COS-3 is reusable for TC; Figure 6 (b) shows the reusability of COS-3 for OTC use; Figure 6 (c) shows the COS-3 capture experiment of TC; Figure 6 In the middle (d), COS-3 captures OTC.
[0029] Figure 7This study explores possible degradation pathways of TC by COS-3.
[0030] Figure 8 This study explores possible degradation pathways of OTC by COS-3.
[0031] Figure 9 In the middle (a), the acute toxicity analysis of TC and the intermediate products P1, P2, P3, P6 and P9 of TC degradation in the COS-3 / PMS system on three aquatic organisms (fish, water fleas and green algae) is shown.
[0032] Figure 9 (b) shows the acute toxicity analysis of TC and COS-3 / PMS system degradation intermediates P4, P5, P3, P6 and P9 on three aquatic organisms (fish, water fleas and green algae).
[0033] Figure 9 (c) shows the acute toxicity analysis of TC and COS-3 / PMS system degradation intermediates P7, P8, P3, P6 and P9 on three aquatic organisms (fish, water fleas and green algae).
[0034] Figure 9 The middle (d) shows the chronic toxicity analysis of TC and COS-3 / PMS system degradation intermediates P1, P2, P3, P6, and P9 on three aquatic organisms (fish, water fleas, and green algae).
[0035] Figure 9 (e) shows the chronic toxicity analysis of TC and the intermediate products P4, P5, P3, P6, and P9 of TC degradation in the COS-3 / PMS system on three aquatic organisms (fish, water fleas, and green algae).
[0036] Figure 9 (f) shows the chronic toxicity analysis of TC and COS-3 / PMS system degradation intermediates P4, P5, P3, P6, and P9 on three aquatic organisms (fish, water fleas, and green algae).
[0037] Figure 10 In the middle (a), the acute toxicity analysis of OTC and COS-3 / PMS system degradation intermediates P1, P2, P3, P4, P8, and P12 on three aquatic organisms (fish, water fleas, and green algae) is shown.
[0038] Figure 10 (b) shows the acute toxicity analysis of OTC and OTC intermediates P5, P6, P7, P4, P8, and P12 from the COS-3 / PMS system on three aquatic organisms (fish, water fleas, and green algae).
[0039] Figure 10(c) shows the acute toxicity analysis of OTC and OTC intermediates P9, P10, P11, P4, P8, and P12 degraded by the COS-3 / PMS system on three aquatic organisms (fish, water fleas, and green algae).
[0040] Figure 10 The middle (d) shows the chronic toxicity analysis of OTC and COS-3 / PMS system degradation intermediates P1, P2, P3, P4, P8, and P12 on three aquatic organisms (fish, water fleas, and green algae).
[0041] Figure 10 In the middle (e), we present the chronic toxicity analysis of OTC and the COS-3 / PMS system-degraded OTC intermediates P5, P6, P7, P4, P8, and P12 on three aquatic organisms (fish, water fleas, and green algae).
[0042] Figure 10 (f) shows the chronic toxicity analysis of OTC and COS-3 / PMS system degradation intermediates P9, P10, P11, P4, P8, and P12 on three aquatic organisms (fish, water fleas, and green algae).
[0043] Figure 11 This is a schematic diagram of the photocatalytic / Fenton-like mechanism of the COS-3 heterojunction. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] Example 1 The preparation method of tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst includes the following steps: (1) 0.6 g of cellulose was dispersed in 300 mL of distilled water to construct a suspension system. The suspension system was stripped using an SM-1200D ultrasonic cell disruptor. The product was then filtered and collected to obtain ultrasonically pretreated cellulose. (2) Prepare activation solution A, activation solution B and two identical chemical plating solutions; then, perform surface activation of the ultrasonically pretreated cellulose in the two activation solutions; after activation, filter out the solid and put it into the two chemical plating solutions for two-stage chemical plating treatment. Finally, obtain cellulose with deposited Cu by filtration, drying and sieving. (3) Place the cellulose with deposited Cu in a muffle furnace, heat and keep it at a constant temperature, cool it to room temperature and take it out to obtain a tubular CuO-Cu2O composite product, named CuO-Cu2O; (4) Take 0.5 g of tubular CuO-Cu2O composite product, put it into the reaction vessel, add 0.15 g of analytical grade thiourea, and then add 80 mL of anhydrous ethanol as the reaction medium. Stir magnetically until the system is mixed evenly and there is no obvious particle agglomeration. (5) Place the reactor in a constant temperature oven, heat it up and keep it at the temperature to carry out the hydrothermal reaction; after the reaction is completed, cool it to room temperature and take out the sample; wash the sample with deionized water and anhydrous ethanol alternately 5 times to remove the residual thiourea and by-products on the surface, dry it, and obtain the final product, named COS-3. In step (1), the ultrasonic power of the stripping process is 500 W, the ultrasonic interval is 3 s, and the time is 1 h; In step (2), the composition of the activation solution A is: 2.4 mL of concentrated hydrochloric acid and 3 g of copper sulfate pentahydrate are added to every 200 mL of distilled water; The composition of the activation solution B is: 2.4 g sodium hydroxide and 3 g sodium borohydride are added to every 200 mL of distilled water; The chemical plating solution is composed of: 15.9 g copper sulfate pentahydrate, 3.9 g potassium sodium tartrate, 8.1 g disodium ethylenediaminetetraacetate, 0.9 g potassium ferrocyanide, and 21 mL formaldehyde solution added to every 300 mL of distilled water. In step (2), the specific operation of surface activation is as follows: first, place it in activation solution A and stir for 15 min, then transfer it to activation solution B and react for 90 s; each time period of the chemical plating treatment is 30 min. In step (3), the temperature is raised to 300°C and kept constant for 6 hours; In step (4), the magnetic stirring time is 30 min; In step (5), the heating rate is 5℃ / min, and the temperature is maintained at 170℃ for 16 h.
[0046] Example 2 The difference from Example 1 is that the amount of analytical grade thiourea used was 0.05 g, otherwise the same. The final product was obtained and named COS-1.
[0047] Example 3 The difference from Example 1 is that the amount of analytical grade thiourea used was 0.1 g, otherwise the same. The final product was obtained and named COS-2.
[0048] Example 4 The difference from Example 1 is that the amount of analytical grade thiourea used was 0.2 g, otherwise the same. The final product was obtained and named COS-4.
[0049] Example 5 The difference from Example 1 is that the amount of analytical grade thiourea used was 0.25 g, otherwise the same. The final product was obtained and named COS-5.
[0050] Example 6 The difference from Example 1 is that the amount of analytical grade thiourea used was 0.3 g, otherwise the same. The final product was obtained and named COS-6.
[0051] Example 7 The difference from Example 1 is that in step (3), the temperature is heated to 350°C, while the rest is the same, to obtain the final product. The crystal structure is basically the same as that of COS-3 in Example 1.
[0052] Comparative Example 1 The difference from Example 1 is that the amount of analytical grade thiourea used was 2 g, otherwise the same. The final product obtained was Cu7S4.
[0053] Comparative Example 2 The difference from Example 1 is that in step (3), the temperature is raised to 250°C, while the rest is the same, to obtain the final product. The low temperature results in a high proportion of Cu2O in the product, with only a very small amount of CuO generated, leading to poor performance of the constructed heterojunction.
[0054] Comparative Example 3 The difference from Example 1 is that in step (3), the temperature is raised to 400°C, while the rest is the same, to obtain the final product. The excessively high temperature results in a high proportion of CuO in the product, with only a very small amount of Cu2O generated, leading to poor performance of the constructed heterojunction.
[0055] Performance testing 1. Degradation performance test method (1) Photocatalytic degradation performance test First, the optimal addition mass of thiourea was investigated to obtain the best-performing photocatalyst. 20 mg of different materials (including COS-1, COS-2, COS-3, COS-4, COS-5, COS-6, CuO-Cu2O, and Cu7S4) were added to 50 mL of reaction solutions (100 mg / L TC solution and 100 mg / L OTC solution, respectively) in a reaction apparatus for photocatalytic experiments. A 300 W xenon lamp (CEL-LB70) was used as the solar light source. The mixture was stirred for 30 min in a dark environment to reach adsorption equilibrium. The photoreaction time was 20 min, and the supernatant was collected at 5-min intervals. After centrifugation, the concentration was measured using a UV-Vis spectrophotometer. The best-performing photocatalyst was determined based on the degradation effect.
[0056] (2) Degradation performance test of the light / Fenton-like synergistic system Subsequently, the optimal amount of PMS was investigated to explore the synergistic effect of COS-3 photocatalysis and Fenton-like reaction. 20 mg of COS-3 and different masses of PMS were placed in 50 mL of reaction solution (100 mg / L TC solution and 100 mg / L OTC solution, respectively) in the reaction apparatus for photocatalysis / Fenton-like experiment. PMS was added during the photoreaction stage, and the remaining steps were consistent with the photocatalytic degradation performance test to determine the optimal amount of PMS.
[0057] 2. Test Results (1) Morphological analysis To understand the surface morphology and elemental distribution of the photocatalyst, TEM, SEM, and EDS tests were performed. Figure 1 The lattice fringe spacings of 0.197 nm, 0.246 nm and 0.252 nm shown in a correspond to the (224) crystal plane of Cu7S4, the (111) crystal plane of Cu2O and the (-111) crystal plane of CuO, respectively. This indicates that CuO-Cu2O was successfully sulfided in the hydrothermal reaction to form a CuO / Cu2O-Cu7S4 composite material. Figure 1 Image b is a scanning electron microscope (SEM) image of COS-3, showing that the original tubular structure of cellulose was successfully preserved. The image on the right is an EDS image, revealing the presence of Cu, O, and S elements. Cu is the most abundant element, accounting for 74.7 wt% of the total mass, followed by O at 16.2 wt% and S at 9.1 wt%. This demonstrates that through chemical plating, oxidation, and sulfidation, Cu, O, and S were uniformly attached to the cellulose surface, successfully constructing a tubular CuO / Cu2O-Cu7S4 composite material.
[0058] The crystal phase composition of the sample was determined using X-ray diffraction. Figure 1As shown in Figure d, the CuO-Cu2O sample exhibits distinct diffraction peaks at 2θ = 36.4°, 42.26°, 61.32°, and 73.53°, which are attributed to the (111), (200), (220), and (311) crystal planes of Cu2O, respectively. The diffraction peaks at 2θ = 35.4° and 38.68° are attributed to the (-111) and (111) crystal planes of CuO, respectively. The diffraction peaks detected in the Cu7S4 sample at 2θ = 27.83°, 32.21°, and 46.14° correspond to the (113), (004), and (224) crystal planes of Cu7S4, respectively. The diffraction patterns of the prepared tubular CuO / Cu2O-Cu7S4 composite materials (COS-1~COS-6) all showed characteristic diffraction peaks of CuO, Cu2O, and Cu7S4, proving the successful preparation of a photocatalytic composite material composed of CuO-Cu2O and Cu7S4, which is consistent with the SEM and TEM test results. Furthermore, with increasing thiourea addition, the intensity of the characteristic diffraction peaks of CuO and Cu2O gradually decreased, while the intensity of the characteristic diffraction peak of Cu7S4 gradually increased. This result confirms that increasing the thiourea addition can effectively increase the relative content of Cu7S4 in the composite material. This study aims to achieve balanced control of the content of CuO-Cu2O and Cu7S4 components to construct a highly efficient photocatalytic material suitable for photocatalytically assisted Fenton reaction systems, achieving efficient degradation of antibiotics.
[0059] Figure 1 In Figure 'e', the adsorption isotherm curves are shown. The test results indicate that the morphology and trend of the isotherms of CuO-Cu2O, Cu7S4, and COS-3 are basically consistent, all exhibiting H1-type hysteresis loops, indicating that each sample possesses a cylindrical pore structure, and their isotherm type can be classified as Type IV. COS-3 exhibits superior adsorption performance because during the hydrothermal reaction, the surface of CuO-Cu2O undergoes sulfidation to generate Cu7S4, forming a rich microporous structure, which is also confirmed by the pore size distribution diagram. Figure 1 (f) This significantly increases the specific surface area of COS-3, making it more conducive to adsorbing pollutants in water and thus enhancing its catalytic activity.
[0060] (2) XPS analysis To investigate the chemical composition, elemental valence state distribution, and interfacial interactions of the CuO / Cu2O-Cu7S4 ternary composite material, the formation mechanism of the heterojunction in COS-3 and the transfer pathway of photogenerated carriers at the interface were elucidated. X-ray photoelectron spectroscopy (XPS) was used to systematically characterize COS-3, CuO-Cu2O, and Cu7S4 control samples, such as... Figure 2 It can be seen that C, Cu, O and S elements can be detected in COS-3, which is consistent with the EDS test results.
[0061] The C 1s peak fitting results show that ( Figure 2 In section a), the composite material exhibits three characteristic peaks at 284.8 eV, 286.28 eV, and 288.02 eV, corresponding to different carbon chemical environments: the main peak at 284.8 eV is attributed to the sp formed by the high-temperature carbonization of cellulose. 2 The hybrid CC / C=C bond is a characteristic signal of the graphitized carbon skeleton, confirming the formation of a stable carbon support after carbonization. The 286.28 eV peak belongs to the CO / C-OH bond, originating from the oxygen-containing functional groups remaining after carbonization and the Cu-OC bonding between the carbon matrix and the metal active component. This provides abundant anchoring sites for the in-situ growth and stable loading of the CuO / Cu2O-Cu7S4 active component. The 288.02 eV peak belongs to the C=O / OC=O bond, corresponding to the carbonyl and carboxyl groups generated during carbonization. This enhances the adsorption capacity of COS-3 and provides additional active sites for the catalytic reaction. In the Cu 2p spectrum ( Figure 2 (b) The characteristic peaks at 932.38 eV and 952.30 eV belong to Cu. + The 2p 3 / 2 and 2p 1 / 2 orbitals, the signal originates from Cu in Cu2O and Cu7S4 lattice. + The characteristic peaks at 934.23 eV and 954.81 eV are attributed to Cu. 2+ Cu at 943.65 eV and 962.66 eV in the 2p 3 / 2 and 2p 1 / 2 orbitals. 2+ The distinctive shock satellite peak further confirms its stable existence; this signal originates from Cu in the CuO and Cu7S4 lattice. 2+ Sites confirm the presence of Cu in the system + / Cu 2+ Mixed valence states coexist stably. (O 1s spectrum) Figure 2 In the S 2p spectrum, the main peak at 531.58 eV corresponds to the lattice oxygen and surface hydroxyl oxygen of CuO and Cu2O, and the secondary peak at 533.18 eV corresponds to the surface adsorbed water and adsorbed oxygen, confirming that the oxide components are completely preserved. Figure 2 The spin splitting characteristic peaks at 161.80 eV and 162.91 eV (d) are attributed to the S-bonds of the Cu-S bonds in the Cu7S4 lattice. 2- The weak peak at 168.80 eV corresponds to a small amount of SO4 generated from surface oxidation. 2- The CuO-Cu2O control sample showed no sulfur signal, confirming the successful introduction of Cu7S4. These results fully demonstrate the successful preparation of the CuO / Cu2O-Cu7S4 ternary composite material.
[0062] The binding energy of XPS characteristic peaks is directly related to the electron cloud density around the atoms, and their shift provides direct experimental evidence for interfacial charge transfer and heterostructure formation. Among these, the peak shifts of S elements, which are distributed only in the sulfide phase, and O elements, which are distributed only in the oxide phase, show no interference from multi-component signal superposition, making them the most reliable criteria for charge transfer. Figure 2 It can be seen that, compared with CuO-Cu2O, the O 1s characteristic peak of COS-3 is significantly shifted to higher binding energies, with the hydroxyl oxygen peak shifting by 0.51 eV. The lattice oxygen peak at the original 529.43 eV has broadened and merged due to the decrease in electron cloud density, indicating that CuO-Cu2O undergoes significant electron loss. Compared with Cu7S4, the 2p 1 / 2 peak of S 2p in COS-3 shifts to lower binding energies by 0.08 eV, indicating that Cu7S4 undergoes electron enrichment. At the same time, the 2p 3 / 2 peak of COS-3 shifts to higher binding energies by 0.25 eV, and the maximum shift of the shock satellite peak reaches 1.32 eV, further corroborating the Cu 1s characteristic peak of CuO-Cu2O. 2+ The regular shift of the aforementioned characteristic peaks reveals a directional charge transfer at the composite material interface: electrons migrate directionally from CuO-Cu2O (higher Fermi level) to Cu7S4 (lower Fermi level) through the closely contacted heterojunction interface. This result confirms the successful construction of the CuO / Cu2O-Cu7S4 ternary heterojunction. The interface-directed charge transfer effectively promotes spatial separation of photogenerated carriers and suppresses electron-hole pair recombination, providing core structural and electronic mechanism support for improving the photocatalytic-persulfate activation synergistic degradation performance of TC and OTC in this material.
[0063] (3) Photoelectric properties and band structure The results of ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS) are as follows: Figure 3 As shown in Figure a, the absorption edge of CuO-Cu2O is approximately 430 nm, with its main response range concentrated in the ultraviolet and near-visible regions; the absorption edge of Cu7S4 is located near 594 nm. In contrast, COS-3 exhibits a significantly enhanced light-harvesting ability, with its absorption edge markedly red-shifted to 670 nm. This significant red-shift indicates that by combining CuO-Cu2O with Cu7S4, the optical bandgap of COS-3 is effectively narrowed, greatly broadening its response range to visible light. Simultaneously, the absorption intensity of COS-3 in the entire visible light region (400-600 nm) is significantly improved compared to the precursor. The bandgap energies of the three materials were quantitatively characterized using the Tauc plot method. Figure 3(b) The results show that the band gap energies of Cu7S4 and CuO-Cu2O are 1.05 eV and 1.10 eV, respectively. The band gap energy of COS-3 was measured to be 1.83 eV, which is highly consistent with the absorption edge of approximately 670 nm in the aforementioned UV-Vis DRS. This moderate band gap width ensures the strong absorption capability of COS-3 in the visible light range. The improvement in optical performance and the significant change in band gap energy are attributed to the heterostructure formed by interfacial coupling between the three components and interfacial charge transfer, which is consistent with the XPS analysis results.
[0064] To further elucidate the charge migration mechanism within the COS-3 heterojunction, the valence band peak (VBM) positions of CuO-Cu2O and Cu7S4 were determined using XPS valence band spectroscopy. Figure 3 c and Figure 3 As shown in Figure d, the VBMs of CuO-Cu2O and Cu7S4 are 1.63 eV and 0.89 eV, respectively. Combining the measured band gap energy, according to the formula E... CB = E VB - E g Calculations show that the conduction band (CB) bottom potentials of the two are 0.53 eV and -0.16 eV, respectively. This staggered band arrangement constitutes a typical heterojunction structure. Cu7S4 has a more negative conduction band potential and a valence band position closer to the Fermi level, which provides a thermodynamic driving force for the directional migration of electrons. Combined with the aforementioned blue shift phenomenon (increased binding energy) in CuO-Cu2O during XPS, it is confirmed that electrons spontaneously flow from CuO-Cu2O to Cu7S4 under the influence of the built-in electric field at the interface. This modulation of the band structure not only explains the optical property of the COS-3 absorption edge redshifting to 670 nm, but more importantly, it achieves the spatial separation of photogenerated carriers: electrons enriched on Cu7S4 can efficiently transfer Cu... 2+ Reduced to active Cu + This continuously activates PMS to generate strong oxidative free radicals, ultimately significantly improving its ability to degrade antibiotics.
[0065] Photoelectrochemical testing further confirmed the modulation effect of the heterojunction on the behavior of photogenerated carriers. Electrochemical impedance spectroscopy (EIS) Figure 3 (e) shows that COS-3 has the smallest Nyquist arc radius among all samples, implying it has the lowest charge transfer resistance. Meanwhile, the transient photocurrent response results ( Figure 3 As shown in f), the photocurrent intensity of the COS-3 composite material is significantly higher than that of CuO-Cu2O and Cu7S4, and it exhibits the strongest photoresponse capability. This indicates that COS-3 has higher photogenerated charge generation and spatial separation efficiency under visible light irradiation compared with other materials.
[0066] Based on the above chemical characterization, the step-wise improvement in COS-3 performance is attributed to the tight heterostructure formed between CuO-Cu2O and Cu7S4. Bandgap modulation red-shifts the absorption edge to 670 nm, increasing carrier generation. The built-in electric field drives electrons to migrate directionally towards Cu7S4, significantly reducing the probability of electron-hole recombination. The extremely low interfacial impedance ensures that electrons can rapidly participate in Cu... 2+ / Cu + The cycle efficiently activates PMS to generate a large number of active oxide species, thereby achieving rapid degradation of antibiotics.
[0067] (4) Photocatalytic / Fenton-like performance analysis To investigate the effect of different component ratios on photocatalytic degradation efficiency, this study first used 100 mg / L TC and OTC as target pollutants and systematically examined the degradation performance of photocatalysts prepared with different thiourea addition amounts under the same experimental conditions.
[0068] The degradation rate and degradation amount were calculated according to formulas (1) and (2) respectively. The degradation of antibiotics is represented by the first-order kinetic equation, formula (3).
[0069] ρ=(C0-C t ) / C0×100%(1) Where: ρ - degradation rate, C0 - initial concentration, C t -Concentration after photocatalysis.
[0070] β=(C0-C t )×V / m0(2) Where: β - degradation amount, C0 - initial concentration, C t - Concentration after photocatalysis, V - Solution volume, m0 - Mass of photocatalyst.
[0071] Ln(C t / C0)= k×t(3) Where: k - apparent rate constant, t - reaction time.
[0072] The degradation rate and degradation amount were quantitatively assessed using formulas (1) and (2), with the experimental time as the X-axis. In (C t Using (C0) as the Y-axis, the first-order reaction rate constant k was obtained through linear fitting, and multi-dimensional comparative analysis confirmed that COS-3 is the optimal photocatalyst in this system. Based on this, the effect of PMS dosage on reaction kinetics was further explored, using COS-3 as a representative example. Finally, the photocatalytic / Fenton-like synergistic degradation performance of COS-3 under visible light-driven conditions and its efficient removal mechanism for typical antibiotics were analyzed in depth.
[0073] Experimental results show that ( Figure 4The component ratio of the catalyst has a significant regulatory effect on the degradation performance. With the increase of thiourea addition in the system, the degradation efficiency of the composite material for antibiotics shows an inverted V-shaped trend of first increasing and then decreasing. Among COS-1 to COS-6, COS-3 exhibits the best catalytic activity, with degradation rates of 39.8% and 43.6% for TC and OTC, respectively, which are 2.34 and 1.59 times that of CuO-Cu2O, and 3.02 and 1.77 times that of Cu7S4, and the corresponding kinetic rate constants are significantly better than those of other ratios and single components. This leap in performance is mainly attributed to the optimal heterojunction coupling effect constructed by a moderate degree of sulfidation: too little sulfidation is insufficient to form a sufficient S-type heterojunction interface, while excessive sulfidation may lead to excessive coating of Cu7S4 on the CuO-Cu2O surface, which not only masks the active sites but may also increase charge transport resistance, thereby inhibiting catalytic activity.
[0074] Furthermore, kinetic studies on PMS dosage show that ( Figure 5 The degradation efficiency exhibited a phased characteristic with increasing PMS dosage. Within the 5-20 mg range, the degradation rate rapidly increased with increasing PMS concentration, reaching a clear inflection point at 20 mg. When the PMS dosage further increased to 25-30 mg, the increase in degradation rate significantly leveled off (TC only slightly increased from 94.9% to 96.0%, and OTC only slightly increased from 95.7% to 96.5%). This phenomenon can be attributed to two factors: firstly, the active sites on the catalyst surface had reached adsorption and activation saturation; secondly, excessive PMS induced a free radical self-quenching effect (such as ·SO4). - With excessive HSO5 - The reaction produces SO5 with a low oxidation potential. - This leads to a decrease in the utilization rate of active species. Taking into account purification efficiency, economic cost, and potential secondary pollution caused by reagent redundancy, the optimal PMS addition amount was determined to be 20 mg, i.e., a mass ratio of photocatalyst COS-3 to PMS of 1:1.
[0075] By comparing the degradation performance of COS-3 in a single photocatalytic system and a COS-3 / PMS photocatalytic / Fenton-like coupled system, a significant step-wise improvement in catalytic efficiency due to the Fenton-like process can be observed. Figure 4 and Figure 5 Experimental results showed that the antibiotic removal efficiency of a single photocatalytic system was limited, while the degradation rate increased explosively after the introduction of 20 mg PMS (the degradation rates of TC and OTC increased by 2.38 and 2.19 times, respectively). This efficient synergistic mechanism can be summarized as follows: the strong reducing electrons generated by the S-type heterojunction constructed by COS-3 under visible light not only effectively suppressed carrier recombination, but also acted as a driving force to promote the interfacial Cu2+ / Cu + Highly efficient cycle. The Cu produced by reduction... + Transiently activated PMS undergoes a Fenton-like reaction, inducing the production of large amounts of ·SO4. - Highly reactive free radicals such as ·OH. This synergistic pathway of "photo-induced reduction-chemical activation" successfully overcomes the bottleneck of slow regeneration of active sites in traditional Fenton-like reactions, enabling the system to achieve deep destruction and efficient removal of the molecular skeleton of typical antibiotics (TC / OTC) in a very short time.
[0076] COS-3 stability and capture experiments The stability and reusability of catalysts are core indicators for evaluating their feasibility in practical wastewater treatment applications. This study used COS-3 to conduct five consecutive cyclic degradation experiments on TC and OTC to assess their long-term performance in a visible-light-activated PMS system. Figure 6 a and Figure 6 As shown in Figure b, after five consecutive cycles, the degradation efficiency of COS-3 for TC remained at 92.5% (only a slight decrease of 2.4% from the initial activity), and the degradation efficiency of COS-3 for OTC remained at 93.7% (only a slight decrease of 2% from the initial activity). COS-3 exhibits good recyclability and demonstrates great potential for long-term application in treating antibiotic-contaminated wastewater.
[0077] To investigate the main active species for antibiotic degradation in the COS-3 photocatalytic / Fenton-like system, 1.0 M methanol (MeOH), 100 mM isopropanol (IPA), 10 mM disodium ethylenediaminetetraacetate (EDTA-2Na), 5 mM p-benzoquinone (BQ), and 20 mM histidine were added to the system as ·SO4. - ·OH, h + O2 - and 1 O2 quencher. Experimental results show that ( Figure 6 c and Figure 6 (d) The addition of MeOH significantly inhibited the degradation of TC and OTC, while IPA and EDTA-2Na showed weaker inhibitory effects, and BQ and L-His showed the worst inhibitory effects. This indicates that SO42- - These are the most essential active species in the system, ·OH and h + Through direct oxidation or the important synergistic effect of induced oxygen reduction reaction, ·O2 - and 1 O2 is an auxiliary path.
[0078] (5) Intermediates of TC and OTC, possible degradation pathways and toxicity analysis Nine major intermediates in the degradation of TC were identified by LC-MS analysis. The three pathways of TC degradation are as follows: Figure 7 As shown. In pathway I, under initial attack by reactive oxidizing species (ROS), the hydroxyl group of the TC molecule undergoes dehydration to generate product P1 (m / z = 427). Subsequently, the dimethylamino group on the side chain of P1 undergoes demethylation or further deamination to transform into P2 (m / z = 414). With the continued attack of the C-C bond by strong oxidizing free radicals, a small molecular fragment P3 (m / z = 135) is generated. In pathway II, the TC molecule first loses its amide group to form intermediate P4 (m / z = 426). Subsequently, under the attack of SO42-... - Under electrophilic attack, the C-C bonds within TC break, leading to ring-opening and generating intermediate P5 (m / z = 347). P5 is further oxidized and cleaved into monocyclic or bicyclic organic compounds P6 (m / z = 166). In pathway III, due to the extremely high addition reactivity of ·OH, it attacks the double bonds or benzene ring of the TC molecule, causing hydroxylation and generating intermediate P7 (m / z = 467). Subsequently, P7 undergoes oxidative recombination to generate P8 (m / z = 454). Under strong oxidizing conditions, these unstable polycyclic products undergo deep oxidation, leading to benzene ring-opening and degradation into small organic acid P9 (m / z = 150). Finally, these intermediates will mineralize into carbon dioxide, water, and small molecules through a series of processes including dehydration, deamination, hydroxylation addition, and skeletal ring-opening.
[0079] Twelve major intermediates in the OTC degradation process were identified by LC-MS analysis. The three pathways of OTC degradation are as follows: Figure 8 As shown. In pathway I, the OTC molecule undergoes hydroxylation under the attack of ·OH, generating P1 (m / z = 480), which is then further converted to P2 (m / z = 424) through demethylation, followed by deamidation and dehydroxylation to generate P3 (m / z = 377). Subsequently, a vigorous photo-oxidation reaction leads to the fragmentation of the molecular structure, producing the smaller molecule P4 (m / z = 144). In pathway II, the amino group adjacent to the OTC carbocyclic ring first undergoes a ring-opening reaction to generate product P5 (m / z = 432). Subsequently, P5 undergoes deamination or decarboxylation to generate product P6 (m / z = 388). Due to ·SO4 -The strong cleavage of the CC-bridged bond causes ring-opening of the A ring of OTC, producing a tricyclic derivative P7 (m / z = 327). P7 is further oxidized and decomposed, eventually transforming into intermediate P8 (m / z = 149) containing a naphthalene ring or a bicyclic structure. In pathway III, the OTC molecule undergoes demethylation under intense ROS attack, removing the methyl group from the dimethylammonium and undergoing deacylation to form intermediate P9 (m / z = 390), which subsequently undergoes ring-opening oxidation, hydroxylation, and decarboxylation to generate intermediate P10 (m / z = 321). Through a series of oxidative recombination processes, it is transformed into P11 (m / z = 245) and finally fragments into the stable phenolic molecule P12 (m / z = 137). Ultimately, these intermediates will be cleaved and mineralized into carbon dioxide, water, and small molecules through a series of oxidation, ring-opening, and elimination processes.
[0080] To assess the ecological safety of the COS-3 / PMS system during environmental remediation, this study used the ECOSAR program in EPI Suite software to predict the acute and chronic toxicity of the main degradation products of TC and OTC to three typical aquatic organisms (fish, water fleas, and green algae). The toxicity assessment results are as follows: Figure 9 and Figure 10 As shown, the higher the value of log LC50 or logEC50, the lower the toxicity of the product.
[0081] The results showed that the original TC and initial products (P1 and P2, etc.) were in the "toxic" or "harmful" zone (0.5–1.5), indicating that simple functional group modification could not eliminate its biotoxicity. A key turning point occurred at stages P3 and P6, where the toxicity value rose to 3.0–5.6, entering the "harmless" zone, which highly coincided with the tetracyclic skeleton breakage confirmed by LC-MS. Although the toxicity of the final products showed slight adjustments, it was still far lower than that of TC. The original OTC was in the "toxic" or "harmful" zone (0.5–1.0). In pathways I and II, the toxicity of the initial products (P1, P2, and P6) decreased significantly, with some entering the harmless zone. Although a temporary rebound in toxicity occurred in the mid-degradation phase due to the formation of unstable intermediates (P8 and P11), as the reaction progressed, the toxicity of the final product P12 was far lower than that of the original OTC. The heatmap confirmed the system's transition from a high-risk to a low-risk zone. In conclusion, the COS-3 / PMS system effectively reduces the ecological risks of TC and OTC through deep oxidation, confirming the environmental safety of this technology.
[0082] (6) Photocatalysis / Fenton-like mechanism analysis This study successfully constructed a highly efficient S-type ternary heterojunction by coupling CuO-Cu2O and Cu7S4, achieving efficient spatial separation of photogenerated carriers and kinetic acceleration of Fenton-like reactions. Based on the UV-Vis diffuse reflectance spectrum, bandgap diagram, and XPS valence band spectrum (…),… Figure 2 and Figure 3 It can construct cross-band structures of CuO-Cu2O and Cu7S4. Figure 11 Band structure analysis and XPS test results ( Figure 2 and Figure 3 This indicates that, under the influence of the built-in electric field, electrons with weak reducing power in the conduction band of CuO-Cu2O recombine with holes with weak oxidizing power in the valence band of Cu7S4 at the interface. This spatially preserves the highly reducing electrons (-0.16 eV) in the Cu7S4 conduction band and the highly oxidizing holes (1.63 eV) in the CuO-Cu2O valence band. This, in turn, generates a large number of reactive oxide species (ROS), such as ·OH and h2O. + O2 - and 1 O2, etc. Furthermore, this unique charge migration pathway not only enhances the redox potential of the system, but more importantly, the high-energy electrons enriched on the Cu7S4 side significantly accelerate Cu… 2+ / Cu + The valence band cycle induces PMS to produce a large amount of SO42-. - This photocatalytic Fenton-like synergistic effect ensures the efficient disintegration and complete mineralization of antibiotics (TC / OTC). The degradation process of this system can be summarized as a deep synergy between photocatalysis and Fenton-like reactions: ·SO4 - As the core active ingredient, it utilizes its high potential and strong selectivity to induce ring-opening of the antibiotic molecular skeleton; ·OH, as a potent oxidant, undertakes the task of further degradation and deep mineralization of intermediate products; photogenerated holes (h + By directly oxidizing surface-adsorbed organic matter and driving charge separation under a built-in electric field, the interfacial charge balance was maintained and the Cu oxidation process was accelerated. 2+ / Cu + Cyclic dynamics; simultaneously, the reduction of conduction band electrons produces ·O2. - While suppressing carrier recombination, it also interacts with non-radical pathways. 1 O2 together constructs a multi-dimensional network of active species. This synergistic effect of free radical and non-free radical pathways is the fundamental mechanism by which COS-3 heterojunctions efficiently degrade antibiotics under visible light.
[0083] In summary, this invention successfully constructed a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst with a hierarchical porous structure using cellulose as a carrier through a series of precisely controlled processes, including chemical copper plating, in-situ oxidation, and hydrothermal sulfidation. Characterization results show that this material perfectly retains the original micron-scale longitudinal channel structure of wood, significantly increasing the specific surface area and extending the visible light response range to 670 nm through interfacial coupling. Electrochemical tests show that COS-3 exhibits the lowest interfacial charge transfer resistance and the highest photocurrent response. In the visible light-assisted activated persulfate (PMS) system, the photocatalytic degradation performance shows an inverted "V"-shaped trend with the degree of sulfidation, with COS-3 showing the best performance. With 20 mg of PMS synergy, the degradation rates of TC and OTC reached 94.9% and 95.7% respectively within 20 min, achieving explosive growth compared to the single photocatalytic system. Mechanism analysis reveals that the S-type heterojunction achieves spatial separation of charge carriers, with the high-energy electrons enriched on the Cu7S4 side significantly accelerating the interfacial Cu... 2+ / Cu + The cycle drives the PMS to generate SO4. - With the core, ·OH and h + A synergistic network of active species was identified. LC-MS pathway analysis confirmed that the active species induce dehydration and deamination of antibiotic molecules through multi-site attack, leading to ring-opening of the core skeleton and its transformation into small organic molecules, which are ultimately mineralized into CO2 and H2O. ECOSAR assessment further confirmed that the intermediates after core skeleton ring-opening significantly reduced the ecotoxicological risk to aquatic organisms. The catalyst maintained an activity retention rate of over 92% after 5 cycles, demonstrating excellent stability and potential for environmental remediation applications.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst, characterized in that, Includes the following steps: (1) Cellulose was dispersed in distilled water to form a suspension system. The suspension system was then subjected to a separation process using an ultrasonic cell disruptor. The product was then collected by filtration to obtain ultrasonically pretreated cellulose. (2) Prepare activation solution A, activation solution B and two identical chemical plating solutions; Subsequently, the ultrasonically pretreated cellulose was surface activated in two activation solutions; After activation, the solid was filtered out and then placed into two separate chemical plating solutions for two-stage chemical plating treatment. Finally, the cellulose with deposited Cu was obtained by filtration, drying and sieving. (3) Place the cellulose with deposited Cu in a muffle furnace, heat and keep it at a constant temperature, cool it to room temperature and take it out to obtain a tubular CuO-Cu2O composite product; (4) Take the tubular CuO-Cu2O composite product and put it into the reaction vessel. Add thiourea and then add anhydrous ethanol as the reaction medium. Stir magnetically until the system is mixed evenly and there is no obvious particle agglomeration. (5) Place the reactor in a constant temperature oven, heat it up and keep it at the temperature to carry out the hydrothermal reaction; after the reaction is completed, cool it to room temperature and take out the sample; wash the sample alternately with deionized water and anhydrous ethanol, dry it, and obtain the final product; In step (3), the temperature is raised to 300-350℃ and kept at a constant temperature for 6 hours; In step (4), the mass ratio of the tubular CuO-Cu2O composite product to thiourea is 10:1-6; The magnetic stirring time is 30 minutes.
2. The method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst according to claim 1, characterized in that, In step (1), the ultrasonic power of the stripping process is 400-600 W, the ultrasonic interval is 3 s, and the time is 1-2 h.
3. The method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst according to claim 1, characterized in that, In step (2), the composition of the activation solution A is: 2.4 mL of concentrated hydrochloric acid and 3 g of copper sulfate pentahydrate are added to every 200 mL of distilled water; The composition of the activation solution B is: 2.4 g sodium hydroxide and 3 g sodium borohydride are added to every 200 mL of distilled water; The chemical plating solution is composed of: 15.9 g copper sulfate pentahydrate, 3.9 g potassium sodium tartrate, 8.1 g disodium ethylenediaminetetraacetate, 0.9 g potassium ferrocyanide, and 21 mL formaldehyde solution added to every 300 mL of distilled water.
4. The method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst according to claim 1, characterized in that, In step (2), the specific operation of surface activation is as follows: first place it in activation solution A and stir for 15 min, then transfer it to activation solution B and react for 90 s; Each electroless plating process lasts for 30 minutes.
5. The method for preparing a tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst according to claim 1, characterized in that, In step (5), the heating rate is 5℃ / min, and the temperature is maintained at 170℃ for 16 h.
6. The tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst obtained by the preparation method according to any one of claims 1-5.
7. The application of the tubular CuO / Cu2O-Cu7S4 ternary heterojunction photocatalyst according to claim 6 in the activation of PMS for the degradation of tetracycline antibiotics in water.
8. The application according to claim 7, characterized in that, The tetracycline antibiotics include tetracycline and oxytetracycline.
